Regulating through disclosure: the case of food hygiene barometer ratings in China. Issue 4 (3rd April 2023) - Wang, Li; Demeritt, David; Rothstein, Henry
Abstract: This paper provides the first assessment of China's twenty-year experiment with food hygiene barometer rating systems, originally developed in the West for publicly communicating the grades awarded by food safety inspectors to individual businesses. This approach to regulating through disclosure is often celebrated for efficiently 'nudging' improved business compliance by empowering consumers to make 'better' decisions, but little is known about disclosure-based regulation in China or other low- and middle-income countries. Combining policy document and quantitative social media analysis with key informant interviews (n = 35), we show that barometers have failed to improve hygiene in China's rapidly expanding private food sector: more than 75% of restaurants in four diverse case-study localities remain merely 'Adequate' with many of those unable in practice to meet basic safety standards. This is because regulatory implementation has been hesitant and unreliable; consumers ignore or distrust barometers; and food businesses lack the capacity and competitive incentive to improve. That failure to empower consumer sovereignty and leverage business behaviour change, however, also reflects how barometers – despite their liberal individualist conceit - were adapted to China's revolutionary 'mass line' traditions of societal supervision of government regulators as much as food businesses. We conclude that barometers – far from being a 'light-touch' alternative to command-and-control regulation- require significant governance capacity, which may be lacking in low- and middle-income countries that struggle to conduct even basic regulatory oversight. Disclosure-based regulation also requires high levels of economic development, formalisation and trust to inculcate consumer and business responsiveness to information disclosures. Finally, our paper contributes to debates about risk communication and regulation by drawing the novel conclusion that the conceits underpinning seemingly universal tools of regulating through disclosure, get adapted to national state traditions and norms in ways that are far removed from their origins.